2014
DOI: 10.1148/radiol.13122670
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Dural Arteriovenous Fistulas: Evaluation with 3-T Four-dimensional MR Angiography Using Arterial Spin Labeling

Abstract: The good-to-excellent agreement between 3-T 4D ASL MR angiographic and DSA findings suggests that 3-T 4D ASL MR angiography is a useful tool for the evaluation of intracranial dural AVFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 10 publications
3
34
0
Order By: Relevance
“…28,29 Our current study demonstrated very good agreement between 3D TOF MRA and DSA findings for the main arte- rial feeders. In assessing main arterial feeders, intermodality agreement is better for 3D TOF MRA than for these 4D MRA techniques.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…28,29 Our current study demonstrated very good agreement between 3D TOF MRA and DSA findings for the main arte- rial feeders. In assessing main arterial feeders, intermodality agreement is better for 3D TOF MRA than for these 4D MRA techniques.…”
Section: Discussionsupporting
confidence: 72%
“…Recent 3T 4-dimensional (4D) MRA techniques, i.e., 4D contrast-enhanced MRA and 4D arterial spin labeling-based MRA, can provide hemodynamic information regarding intracranial DAVFs, [28][29][30] but these techniques are not so reliable for assessing arterial feeders of DAVFs. 28,29 Our current study demonstrated very good agreement between 3D TOF MRA and DSA findings for the main arte- rial feeders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a similar sequence to silent MRA, Iryo et al 24 reported the contrast inherent inflow-enhanced multiphase angiography, or CINEMA, sequence. The CINEMA sequence is a non-contrastenhanced MRA using arterial spin-labeling, such as silent MRA.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial spin labeling (ASL) techniques are used both for noncontrast 4D‐MRA as well as for perfusion imaging. Because both imaging modalities are based on a similar ASL preparation module, a combined acquisition seems feasible.…”
Section: Introductionmentioning
confidence: 99%